2020
DOI: 10.1108/ijoem-03-2019-0231
|View full text |Cite
|
Sign up to set email alerts
|

CEOs' experience and career success in Latin American firms

Abstract: PurposeThis study investigates the influence of experience – organisational tenure, international experience and springboard role – upon Chief Executive Officers’ (CEOs) time to the top and the time taken by CEOs to reach that position. As work and careers are embedded in economic and institutional environments, although prior Western career studies have explored this relationship, this study aims to determine the suitability of experience as a human capital attribute to explain CEO career success in Latin Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…We claim that time to the top is not necessarily equal to reaching the CEO position, but it is equal to reaching a management board position. With this approach, we extend previous studies focusing on the time it takes to become CEO (e.g., Blanco & Sastre Castillo, 2020;Georgakakis et al, 2016;Hamori & Kakarika, 2009;Rovelli & Curnis, 2020;Salvato et al, 2012). By considering the number of industries, employers, functions and countries, we offer a comprehensive perspective on career variety as a predictor of the time it takes to reach the top.…”
Section: Contributionsmentioning
confidence: 60%
See 2 more Smart Citations
“…We claim that time to the top is not necessarily equal to reaching the CEO position, but it is equal to reaching a management board position. With this approach, we extend previous studies focusing on the time it takes to become CEO (e.g., Blanco & Sastre Castillo, 2020;Georgakakis et al, 2016;Hamori & Kakarika, 2009;Rovelli & Curnis, 2020;Salvato et al, 2012). By considering the number of industries, employers, functions and countries, we offer a comprehensive perspective on career variety as a predictor of the time it takes to reach the top.…”
Section: Contributionsmentioning
confidence: 60%
“…However, while human capital theory makes us assume that more career variety accelerates the ascent to the top, we know from previous studies that we reviewed above that this is not necessarily the case: for instance, employer variety as well as industry variety can be detrimental for social capital (Blanco & Sastre Castillo, 2020;Hamori & Kakarika, 2009). In addition, spending parts of the career in other countries increases country variety, but may isolate a potential C-suite candidate from power networks and the elite circles in the home country (Schmid & Wurster, 2017).…”
Section: The Boundaryless Career Approach and Career Varietymentioning
confidence: 97%
See 1 more Smart Citation
“…Despite the fact that CEOs nowadays spend less time within one company than their colleagues did several decades ago, a greater proportion of their careers still takes place in the same firm (Koch et al , 2017). In Latin American companies, having spent one's entire professional career in a single firm -lifetime CEO- and having spent a larger fraction of the career in a firm have been found to reduce CEO time to the top (Blanco and Sastre Castillo, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While Hamori and Koyuncu (2011) and Georgakakis et al (2016) showed that CEOs with higher educational qualifications, in Europe and the United States, climbed the corporate ladder more quickly, Koch et al (2017) found that the time to the top of 100 Fortune CEOs, in the United States, who held a graduate degree did not differ significantly from those who lacked such credentials. In turn, with regard to experience, Hamori and Kakarika (2009) as well as Blanco and Sastre Castillo (2020), having examined respectively CEOs' careers in Europe and the United States, and in Latin America, found that executives who had spent a smaller fraction of their careers in their current organization or who had changed employers more often, had taken longer to reach the CEO post. Indeed, having spent one's entire professional career in a single company – lifetime CEO – was found to reduce the time to the top in Latin America.…”
Section: Introductionmentioning
confidence: 99%